How to strengthen primary health care services in Sri Lanka to meet the future challenges - Sunil Senanayake; Buddhika Senanayake; Thushara Ranasinghe; Neelamani S. R. Hewageegana (College of Community Physicians of Sri Lanka, 2017)
Despite being a lower middle income country, Sri Lanka has achieved commendable health indicators. The main contributory factor for this achievement lies with the policy of 'free education' and provision of health care services free of charge to the people at the point of delivery. Despite the success, Sri Lanka is currently experiencing an epidemiological transition, where the burden of diseases has shifted from communicable diseases to the non-communicable diseases (NCDs). Strengthening primary health care (PHC) with comprehensive community-based and family-focused care is the solitary solution to address the existing health issues in Sri Lanka. Four strategic approaches have been identified. First strategy is to adopt PHC based lifecourse approach and task shifting of PHC workers to combat NCDs, while maintaining the three tier health service model. Innovative public health interventions need to be implemented through primordial, primary, secondary and tertiary prevention levels. Second strategy is to re-model and re-orient Primary Medical Care (PMC) units in the country, by establishing a 'general practitioner (GP) system' to link the preventive and curative PHC services at divisional level. Third strategy is to establish a referral and gatekeeping system to minimize the bypassing of PHC services. Final strategy is to introduce electronic medical record systems to minimize compartmentalization of treatment and to improve the continuum of care. Health authorities should consider these first-hand approaches in their health master plans and attempt to re-orient the health services to meet future health challenges.